Anti-glioma effect of intracranial vaccination with tumor cell lysate plus flagellin in mice. Issue 52 (18th December 2018) - Dong, Boqi; Wang, Liying; Nie, Shu; Li, Xin; Xiao, Yue; Yang, Lei; Meng, Xiuping; Zhao, Peiyan; Cui, Cuiyun; Tu, Liqun; Lu, Wenting; Sun, Wei; et al.
Highlights: TCL plus flagellin prolong the survival of the GL261-bearing mice. Flagellin assists the TCL to induce the anti-glioma immunity. Intracranial administration of flagellin recruits T cells to brain. Intracranial administration of flagellin induces proliferation of T cells. Abstract: The adjuvant effects of flagellin on regulation of immune response have been proved; whether flagellin could assist tumor cell lysate (TCL) to enhance anti-glioma immunity remains to be investigated. This study tests a hypothesis that therapeuticly intracranial administration with flagellin plus TCL enhances the effects of specific immunotherapy on glioma in mice. In this study, GL261 cells were transferred into C57BL/6 mice and the GL261-bearing mice were subcutaneously or intracranially inoculated with flagellin plus TCL, flagellin, TCL or saline. Our results showed that prophylacticly subcutaneous administration with TCL and flagellin could induce potent cytotoxic T lymphocyte (CTL) and prolong the survival of GL261-bearing mice significantly, but therapeuticly subcutaneous administration failed to. However, therapeuticly intracranial administration of TCL plus flagellin could prolong the survival. Moreover, intracranial administration of flagellin could recruit CD4 + T cells and CD8 + T cells to brain tissues, induce proliferation of natural killer (NK) cells, CD4 + T cells and CD8 + T cells in peripheral blood mononuclear cells and induce to splenomegaly. The results suggested that flagellin could be acted as an efficient adjuvant for TCL based vaccine.